FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Angela Angela; Yanti Yanti (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to empirically examine the influence of financial leverage measured by Debt to Total asset (DAR), dividend policy measured by Dividend Payout Ratio (DPR), and Sales Growth measured by Sales Growth (SG) toward firm value measured by Tobin’s Q with firm size measured by Logaritma natural Total Asset (LnTA) as controlling variable. This study uses secondary data obtained from the Indonesia Stock Exchange official website. The population of this study is the manufacturing companies listed on the Indonesia Stock Exchange for the period of 2017-2019. Based on several criteria, 52 manufacturing companies listed on the Indonesia Stock Exchange are selected as samples in this study. This samples are determined using purposive sampling method. The method of analysis was multiple linear regression using Eviews 11 student version. The results of this study indicate that financial leverage has not effect on firm value, while dividend policy and sales growth have a positive and significant effect on firm value. Firm size as a controlling variable has a negative and significant effect on firm value.